Diaphragm pacing in ventilatory failure. Issue 6298 (17th October 1981) - Lozewicz, S; Potter, D R; Costello, J F; Moyle, J B; Maccabe, J J
Abstract : Diaphragm pacing, which entails electrical stimulation to the phrenic nerve, is an effective means of managing patients with ventilatory insufficiency and intact lowermotor-neurone innervation of the diaphragm. The pacing apparatus is used to pace the right and left hemidiaphragms alternately to avoid fatigue, which may damage the muscle irreversibly. Among the important benefits of pacing in quadriplegics with paralysis or respiratory muscles are the social and psychological advantages of not being dependent on a mechanical ventilator.